The Impact of Marital Withdrawal and Secure Base Script Knowledge on Mothers’ and Fathers’ Parenting - Trumbell, Jill M. (J Fam Psychol, 2018)
The current study examines associations between marital conflict and negative parenting behaviors among fathers and mothers, and the extent to which internal working models of attachment relationships may serve as sources of risk or resilience during family interactions. The sample consisted of 115 families (mothers, fathers, and their six-month-old infants) who participated in a controlled experiment. Couples were randomly assigned to engage in either a conflict or positive marital discussion, followed by parent-infant freeplay sessions and assessment of parental internal working models of attachment (i.e., secure base script knowledge). While no differences in parenting behaviors emerged between the conflict and positive groups, findings revealed that couple withdrawal during the marital discussion was related to more intrusive and emotionally disengaged parenting for mothers and fathers. Interestingly, secure base script knowledge was inversely related to intrusion and emotional disengagement for fathers, but not for mothers. Furthermore, only among fathers did secure base script knowledge serve to significantly buffer the impact of marital disengagement on negative parenting (emotional disengagement). Findings are discussed using a family systems framework and expand our understanding of families, and family members, at risk.